A Study of Autonomous Mobile Robot - Nam-Long Doan; Viet-Thinh Dao; Hoang-Ha Nguyen; Pham-Kien-Quoc Luong; Tran-Thanh-Thuy Nguyen; Quang-Thuan Ho; Thai-Duong Nguyen; Khanh-Dang Nguyen; Binh-Hau Nguyen Nguyen; Anh-Duc Nguyen; Phuong-Quang Nguyen; Viet-Khoi Vo; Van-Dong-Hai Nguyen (Journal of Fuzzy Systems and Control, 2025)
With the rapid development of Industry 4.0, automation in production and operations is an important factor to optimize the production process. One of the most important technologies is autonomous mobile robots (AMR). The use of AMR in factories, workshops, and warehouses is becoming more and more popular. Flexibility in production helps companies better meet customer needs and increase productivity without incurring costs and wasting resources. In this study, we present the design and fabrication of an AMR vehicle system for factory environments. The system is developed on Ubuntu and the robot operating system (ROS). Innovation of AMR in our project is to emphasize the change when integrating a ROS-based distributed architecture, in which a separate embedded controller (Raspberry Pi 4 embedded computer) handles real-time control, and a localization and mapping (SLAM) task processor, along with the Navigation Stack package, is used for remote mapping and navigation. Industrial floors are often full of obstacles, so a powerful LiDAR filter and a robust SLAM pipeline are needed to improve mapping accuracy and collision avoidance. This is certainly a promising solution, while current research on autonomous mobile robots usually focuses on navigation and does not incorporate mechanical lifting mechanisms for material handling, we also improve the communication protocol to enhance system performance. Experiments show that the system can automatically position, meet scalability, improve real-time performance, and enable robots to lift/lower objects within the same ROS system, which is suitable for real-world warehouse and factory applications.